Double Lumen Polyamide Tube-stent for the Treatment of Recurrent Postcorrosive Esophageal Stenosis. Issue 5 (May 2017) - Woynarowski, Marek; Dądalski, Maciej; Wojno, Violetta; Teisseyre, Mikołaj; Hurkała, Leszek; Płowiecki, Emil
Abstract : ABSTRACT: This article presents the results of endoscopic treatment for recurrent postcorrosive esophageal stenosis with a tube-stent developed at our institution. The tube-stent was implanted in 5 children with corrosive esophageal injury at the age of 2 to 8.5 years after 7 to 64 dilatation sessions during 5 to 118 months. In total, 13 tube-stents were implanted. One patient had undergone 9 procedures during 2.5 years and the tube-stent remained in place for 14 to 250 days. This patient was tube-stent–dependent due to the lack of any possibility of surgical reconstruction. Two patients had the tube-stent removed after 150 to 205 days and they remain free from esophageal restenosis. One patient did not tolerate the tube-stent, evacuated it after 1 day and was referred for surgical esophagus replacement. One patient is currently still being treated with the tube-stent. Tube-stent was well tolerated and it may be effective in children with recurrent critical postcorrosive esophageal stenosis.